2020
DOI: 10.1101/2020.06.23.166587
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nanoparticle Tracking Analysis: A powerful tool for characterizing magnetosome preparations

Abstract: Nanoparticle Tracking Analysis (NTA) has been employed to measure the particle concentration and size distribution of magnetosomes extracted and purified from Magnetospirillum gryphiswaldense MSR-1, and then exposed to probe ultrasonication for various times, or 1% (w/v) sodium dodecyl sulphate (SDS) for 1 h. Particle concentration increased 3.7-fold over the first 15 min of ultrasonication (from 2 × 10 8 to >7.3 × 10 8 particles mL -1 ), but fell steeply to ~3.6 × 10 8 particles mL -1 after 20 min. NTA of unt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Lysozyme had previously been used to study periplasmatic and cytoplasmatic fractions in MTB cells ( Noguchi et al, 1999 ; Suzuki et al, 2007 ), but very few studies have used this enzyme for magnetosome extraction ( Nakamura et al, 1991 ). French press ( Grünberg et al, 2004 ; Curcio et al, 2020 ), high-pressure homogenization ( Tang et al, 2012 ; Amor et al, 2014 ; Fernández-Castané et al, 2021 ) or sonication ( Kobayashi et al, 2006 ; Alphandéry and Chebbi, 2012 ) are more commonly used for disruption of MTB due to their simplicity and cost-effectiveness. The effect of these disruption techniques on magnetosome chains has not been studied in detail yet, but large aggregates have been observed when the magnetosome membrane is removed.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Lysozyme had previously been used to study periplasmatic and cytoplasmatic fractions in MTB cells ( Noguchi et al, 1999 ; Suzuki et al, 2007 ), but very few studies have used this enzyme for magnetosome extraction ( Nakamura et al, 1991 ). French press ( Grünberg et al, 2004 ; Curcio et al, 2020 ), high-pressure homogenization ( Tang et al, 2012 ; Amor et al, 2014 ; Fernández-Castané et al, 2021 ) or sonication ( Kobayashi et al, 2006 ; Alphandéry and Chebbi, 2012 ) are more commonly used for disruption of MTB due to their simplicity and cost-effectiveness. The effect of these disruption techniques on magnetosome chains has not been studied in detail yet, but large aggregates have been observed when the magnetosome membrane is removed.…”
Section: Resultsmentioning
confidence: 99%
“…As a result of chain breakage, short chains which were not present in pre-disrupted MSR-1 cells were detected after cell disruption. HPH treatment seemed to be the technique that generated less damage to the chains, yielding the lowest short-chain frequency (4%) and the highest long-chain frequency (66%) ( Alphandéry et al, 2013 ; Li, 2018 ; Fernández-Castané et al, 2021 ). The results also revealed that EZ treatment most significantly affected the chain integrity as only 34% of the chains were considered long and 17% short.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations